Ghost diffraction: A spatial statistical approach - (:unkn) unknown (Elsevier B.V., 2023)
We report a new method to reconstruct a two-dimensional object in Ghost diffraction scheme using a spatial statistical optics approach. This is implemented by using a static diffuser rather than a pseudo thermal light source generated with a rotating diffuser as used in conventional ghost imaging systems. The experimental implementation makes use of spatial ergodicity and spatial stationarity for spatially distributed random fields by following an analogy between time average and space average. The ensemble average is replaced by space average under the condition of spatial stationarity and ergodicity. A strategy to realize the Ghost diffraction scheme through spatial intensity correlation with a phase retrieval algorithm permits reconstruction of the transparency. © 2022 Elsevier B.V.
Keywords: Imaging; Phase retrieval; Scattering media; Speckle